2021
DOI: 10.51620/0869-2084-2021-66-9-533-538
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic significance of the soluble form of the VISTA immunity control point in patients with primary bone tumors

Abstract: The data of a comparative enzyme-linked immunosorbent assay of the content of the soluble form of the immunity checkpoint VISTA in the blood serum of 30 healthy donors (control group), 79 patients with primary malignant (osteosarcoma - 30, chondrosarcoma - 31, chordoma - 14) and 14 borderline (giant cell tumor) bone neoplasms are presented. In the general group of patients with malignant neoplasms of bones, the median sVISTA content in blood serum is statistically significant lower than in the control (p = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Likewise, gene polymorphisms are increasingly being linked with the onset of cancer ( 31 ). GnRH2 gene polymorphisms have been linked with bone cancer ( 61 , 62 ). Thus, GnRH2 and GnRHR2 may be novel, unexploited cancer targets.…”
Section: Gnrh2 and Gnrhr2 In Human Reproductive Cancersmentioning
confidence: 99%
“…Likewise, gene polymorphisms are increasingly being linked with the onset of cancer ( 31 ). GnRH2 gene polymorphisms have been linked with bone cancer ( 61 , 62 ). Thus, GnRH2 and GnRHR2 may be novel, unexploited cancer targets.…”
Section: Gnrh2 and Gnrhr2 In Human Reproductive Cancersmentioning
confidence: 99%
“…Kushlinskii et al. conducted ELISA detection for soluble PD-1 (sPD-1), soluble PD-L1 (sPD-L1) and soluble VISTA (sVISTA) in the peripheral blood of chordoma patients and found that there were higher expression of sPD-L1 and lower expression of sVISTA in chordoma patient than in control, no matter the tumor location, stage, tumor type, patient age and gender ( 46 , 47 ), suggesting that chordoma could affect the expression of soluble immune checkpoints and might affect the immune status of the whole body.…”
Section: Immune Microenvironment Characteristics Of Chordomamentioning
confidence: 99%